2021
DOI: 10.1016/j.molcel.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical autophagy drives alternative ATG8 conjugation to phosphatidylserine

Abstract: Highlights d ATG8 can undergo alternative conjugation to phosphatidylserine in cells d ATG8-PS occurs during non-canonical autophagy via singlemembrane ATG8 conjugation d ATG8-PS can be induced by LAP, influenza A, and lysosomal ionic imbalance d ATG8-PS undergoes differential delipidation by ATG4 isoforms

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 56 publications
0
94
0
3
Order By: Relevance
“…We have shown that LC3 can also become conjugated to phosphatidylserine (PS)-enriched membranes during non-canonical autophagy. ATG4D, but not the other paralogs, appears to be uniquely capable for the de-conjugation of LC3-PS in vitro ( Durgan et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that LC3 can also become conjugated to phosphatidylserine (PS)-enriched membranes during non-canonical autophagy. ATG4D, but not the other paralogs, appears to be uniquely capable for the de-conjugation of LC3-PS in vitro ( Durgan et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…ATG4D is the least well-characterized paralog, in part due to low in vitro activity of bacterially expressed protein ( Kauffman et al., 2018 ). Elsewhere, we describe a role for ATG4D in delipidation of PS-conjugated LC3, which accumulates during WD40 CTD-dependent LC3 lipidation, including in response to IAV M2, but not during canonical autophagy ( Durgan et al., 2021 ). While ATG4D exhibited a higher propensity to delipidate PS-conjugated ATG8s than ATG4B in vitro in that study, ATG4B could delipidate ATG8-PS in cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our recent study [ 1 ], we considered the fact that distinct autophagy-related pathways target different membranes, and therefore revisited the analysis of Atg8-family protein lipidation. By combining CRISPR and pharmacological approaches, robust and specific activation of either canonical or non-canonical autophagy was induced.…”
Section: Mainmentioning
confidence: 99%
“…Ubiquitylation of proteins often occurs on misfolded and aggregated proteins caused by stressors as well as under unperturbed conditions, modulating normal protein activity, localization, and their interactions (Figure 1A). Atg8ylation is a process whereby the Atg8 conjugation machinery is recruited to damaged or otherwise stressed membranes or to membranes undergoing remodeling under various homeostatic or non-homeostatic conditions (Figure 1B) and catalyzes mAtg8s' conjugation to phosphatidylethanolamine (PE) [16][17][18], or phosphatidylserine (PS) [18]. Like ubiquitylation, Atg8ylation involves an E1-like activating protein, ATG7 and requires ATP for activation (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%